1979
DOI: 10.1177/030098587901600410
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Nephropathy Induced by Long-Term Ingestion of Ochratoxin A

Abstract: Abstract. Nine pigs were fed crystalline ochratoxin A in their feed at a concentration of about I mg/kg. Three pigs and their controls were killed after 3 months and 6 pigs and controls were killed after 2 years. A decrease of the ratio TmlB..tI1/CI,,. increased urinary glucose excretion and decreased ability to concentrate urine. occurred within a few weeks and aggravated slightly during the 2-year period. Changes in renal structure. characterized by degeneration and atrophy of proximal tubules. interstitial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 7 publications
0
27
0
2
Order By: Relevance
“…The most sensitive parameter was a decrease in the maximum tubular excretion ( T M ) of p -aminohippuric acid (PAH) at all dose levels. In a subsequent 2-year study, six pigs per group were exposed to a single dose level of 40 µg OTA kgbw −1 per day (Krogh et al 1979) resulting in a more severe nephropathy at 2 years compared with 14 weeks based on histopathology, decreased urine osmolality, and increased glucose excretion. Thus, a NOAEL or LOAEL could not be derived from this single-dose study.…”
Section: Hazard Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The most sensitive parameter was a decrease in the maximum tubular excretion ( T M ) of p -aminohippuric acid (PAH) at all dose levels. In a subsequent 2-year study, six pigs per group were exposed to a single dose level of 40 µg OTA kgbw −1 per day (Krogh et al 1979) resulting in a more severe nephropathy at 2 years compared with 14 weeks based on histopathology, decreased urine osmolality, and increased glucose excretion. Thus, a NOAEL or LOAEL could not be derived from this single-dose study.…”
Section: Hazard Identificationmentioning
confidence: 99%
“…Even if OTA were to be regulated as a threshold carcinogen and nephrotoxicity in pigs used as an endpoint, the available 90-day study in pigs (Krogh et al 1974, 1979, see Hazard Identification) has several limitations. Our review of the recent EFSA Opinion (2006) revealed several methodological issues related to the choice of uncertainty factors applied to the endpoint of nephrotoxicity (Table 2).…”
Section: Hazard Characterizationmentioning
confidence: 99%
“…Kuiper-Goodman et al (2010) applied an additional uncertainty factor of two to extrapolate the 90-day subchronic study to a chronic study (this is a default that is consistent with other risk-assessment methodologies). However, in other longer term pig studies, such as the follow-up study by Krogh et al (1979), the exposure of pigs to approximately 40 μg/kg body weight/day for up to 2 years led to progressive nephropathy but no renal failure (EFSA, 2006). Hence, the changes in renal function occurring at the lower dose of 8 μg/kg body weight/day in the 90-day study would not have been expected to progress to renal failure should exposure have been continued.…”
Section: Nongenotoxic Modes Of Actionmentioning
confidence: 99%
“…The lowest observed-effect level of 8 μg/kg body weight/day was determined from a 90-day subchronic study, in groups of 6 to 11 pigs, in which renal enzyme changes, and changes in renal function were noted at all doses (Krogh et al, 1974). In a follow-up study (Krogh et al, 1979), exposure of six pigs to approximately 40 μg/kg body weight/day for 2 years led to progressive nephropathy but not renal failure. One striking difference observed in the kinetics of OTA in the pig, which may explain this species greater sensitivity to OTA is provided by work of Hagelberg et al (1989) who calculated clearance of OTA by renal filtration using glomerular filtration rates and concentrations of free fractions of OTA in plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoxicosis, severely affected the development of broiler as well egg production in layers and produced symptoms like anemia, enlargement of hemorrhagic liver, fat accumulation, kidney paleness and reduced feed uptake [2,3] . Another important mycotoxin in poultry diet is Ochratoxin A (OTA ), which is produced by Aspergillus and Penicillium species of fungi, and have carcinogenic effects especially on kidney and liver [4][5][6] . Lowlevel exposure to OTA leads to reduced feed consumption and increase susceptibility to diseases [7] .…”
Section: Introductionmentioning
confidence: 99%